LITERASI DAN INKLUSI KEUANGAN MELALUI PROGRAM BERORIENTASI LINGKUNGAN - Pangestuti, Dinik Fitri Rahajeng; Mun Yah Zahiroh (Jurnal Berdaya Mandiri, 2023)
This research is a community service-based research that aims to increase financial literacy and inclusion. The method used is Community Based Research. The literacy process is carried out using an Android-based application media. In contrast, the inclusion aspect is carried out by managing waste into financial assets in gold, shares, DPLK, and other financial service products so that economic barriers are no longer obstacles to owning financial assets. The results of this study indicate that the community who become service partners feel that the literacy and inclusion program is beneficial. The assessment is measured using the Net Promoter Score (NPS) measurement tool, which is strengthened by qualitative data and measured by referring to the Alderfer ERG Theory. Keywords: Literacy, Inclusion, Financial Assets, NPS, SUS